The genetic basis for the adaptation of E. coli to sugar synthesis from CO2. Issue 1 (December 2017) - Herz, Elad; Antonovsky, Niv; Bar-On, Yinon; Davidi, Dan; Gleizer, Shmuel; Prywes, Noam; Noda-Garcia, Lianet; Lyn Frisch, Keren; Zohar, Yehudit; Wernick, David; Savidor, Alon; Barenholz, Uri; et al.
Abstract Understanding the evolution of a new metabolic capability in full mechanistic detail is challenging, as causative mutations may be masked by non-essential "hitchhiking" mutations accumulated during the evolutionary trajectory. We have previously used adaptive laboratory evolution of a rationally engineered ancestor to generate anEscherichia coli strain able to utilize CO2 fixation for sugar synthesis. Here, we reveal the genetic basis underlying this metabolic transition. Five mutations are sufficient to enable robust growth when a non-native Calvin–Benson–Bassham cycle provides all the sugar-derived metabolic building blocks. These mutations are found either in enzymes that affect the efflux of intermediates from the autocatalytic CO2 fixation cycle toward biomass (prs, serA, andpgi ), or in key regulators of carbon metabolism (crp andppsR ). Using suppressor analysis, we show that a decrease in catalytic capacity is a common feature of all mutations found in enzymes. These findings highlight the enzymatic constraints that are essential to the metabolic stability of autocatalytic cycles and are relevant to future efforts in constructing non-native carbon fixation pathways. AnE. coli strain able to use CO2 fixation for sugar synthesis was previously generated by experimental evolution of an engineered strain. Here, Herz et al. show that specific mutations in five genes, encoding carbon metabolism enzymes or key regulators, are sufficient to enable robust growth of the strain.